2018
DOI: 10.1108/lht-04-2017-0074
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing people’s health knowledge adoption in social media

Abstract: Purpose The purpose of this paper is to explore the factors influencing people’s health knowledge adoption in social media, with an eye toward promoting health information literacy and healthy behavior. Design/methodology/approach Based on the integration of sense-making theory, social influence theory, information richness theory, fear appeal theory, and ELM (elaboration likelihood method), a health knowledge adoption model is constructed. Taking spondylopathy as an example, high health threat and low healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 82 publications
(93 reference statements)
1
55
2
2
Order By: Relevance
“…This may have accounted for the largest representation of the sample in the Trust Government segment (49%). Trust also seemed to be affective and interpersonal-based, driven by the consumer's experience and intuition about the honesty and reassurance in the crisis knowledge that was communicated (Brengman & Karimov, 2012;Huo et al, 2018). Both the government and cruise companies appeared to have considered public opinion and generated public goodwill in the past (Renn & Levine, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have accounted for the largest representation of the sample in the Trust Government segment (49%). Trust also seemed to be affective and interpersonal-based, driven by the consumer's experience and intuition about the honesty and reassurance in the crisis knowledge that was communicated (Brengman & Karimov, 2012;Huo et al, 2018). Both the government and cruise companies appeared to have considered public opinion and generated public goodwill in the past (Renn & Levine, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Institutional trust is inspired through guarantees from rules and objective quality assurance methods, whereas interpersonal trust is formed through reputationrelated methods, such as user ratings and pricing (Arvanitidis et al, 2020). The formation of trust is underpinned by sense-making theory (Dervin, 1992), which contends that the quality of the communication influences interpretation, content selection and trust (Huo et al, 2018). Clearly, governments and cruise companies are key agencies that consumers are likely to consult in planning their next cruise.…”
Section: Trustmentioning
confidence: 99%
“…One such alternative is social endorsement. Visible social endorsement, e.g., "likes, " (11) enables those with low eHealth literacy to determine trust based on the bandwagon heuristic and assume that, if the source has already been deemed valid by others, then it is safe for them to trust it too (10,12). Traditional 1 Misinformation is incorrect information that stems from human error e.g., a lack of fact checking, whereas disinformation is purposefully and deliberately incorrect.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies, including a particularly compelling one by Chen et al [ 49 ], have shown that individuals with lower eHealth literacy lack the skills necessary to determine the credibility of the source accurately, thus placing their trust in inappropriate sources of information, like social media posts. One potential reason for this is that social endorsement (ie, likes and shares) acts as a signal of perceived trustworthiness to those with lower eHealth literacy [ 48 , 50 - 52 ]. Thus, if social endorsement is having at least a minor impact on the extent to which individuals trust health information that they read online, it is questionable whether they are genuinely making an autonomous decision about which information to treat as credible and act upon.…”
Section: Justifying Interventionmentioning
confidence: 99%